2019
DOI: 10.1016/j.indcrop.2019.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Carlina oxide from Carlina acaulis root essential oil acts as a potent mosquito larvicide

Abstract: Background: One of the most important causative agents of visceral leishmaniasis (VL) is Leishmania infantum, which is mainly spread by Phlebotomus and Lutzomyia sandflies in the Old and New World, respectively. Novel and effective drugs to manage this neglected vector-borne disease are urgently required. In this study, we evaluated the toxicity of carvacrol, thymol and linalool, three common essential oil constituents, on amastigotes and promastigotes of L. infantum. Methods: in vitro experiments were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 103 publications
6
54
0
3
Order By: Relevance
“…Through gas chromatography–mass spectrometry (GC–MS) analysis, the EO extracted from the roots of C . acaulis was characterised and the data obtained were in accordance with the work of Benelli et al [ 56 ]. Seven compounds were identified, among which carlina oxide was the predominant EO component, comprising 94.6% of the relative content.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Through gas chromatography–mass spectrometry (GC–MS) analysis, the EO extracted from the roots of C . acaulis was characterised and the data obtained were in accordance with the work of Benelli et al [ 56 ]. Seven compounds were identified, among which carlina oxide was the predominant EO component, comprising 94.6% of the relative content.…”
Section: Resultssupporting
confidence: 82%
“…Herein, we decided to deepen our knowledge about EO and EO-based NE effectiveness against this harmful insect pest. For this purpose, we selected the EO obtained from the root of Carlina acaulis L. (Asteraceae), which has revealed to be promising as an active ingredient of botanical insecticides, highly effective against vectors and stored product insects [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large difference in the CO content between the soil-grown plants and hydroponic plants may be related to both different growth conditions and the age of the plant [31,32]. Taking into consideration the latest research on insecticidal activity of CO, which showed that CO is a very effective insecticide [14], it should be assumed that this compound can be used for plant protection in the future. CO is found in only a few plant species and soil cultivation of C. acaulis can be a promising way to obtain it.…”
Section: Hplc-pda Analysismentioning
confidence: 99%
“…Both roots and aboveground parts of the plant are used as diaphoretic, diuretic, anthelmintic, and antibacterial drugs in ethnomedicine in Italy [2,3], Montenegro, Bosnia and Herzegovina, Serbia [4], and Macedonia [5]. The biological activity of extracts from Carlina plants is associated with the presence of such compounds as pentacyclic triterpenes: oleanolic (OA) and ursolic acids (UA) [6], chlorogenic acid (ChA), and 3,5-di-caffeoylquinic acid (3,5CQA) [7,8]; flavonoids: vitexin, orientin, homoorientin and schaftoside [9,10]; and carlina oxide (CO) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%